Analisis Potensi dan Rekomendasi Teknis Penerapan Microgrid Berbasis Energi Terbarukan untuk Ketahanan Energi Desa Pasca Bencana - Fathiah, Fathiah; Sri Indah Setiyaningsih; Alfina; Darwani (Seumike : Society Progress Journal, 2026)
Ensuring electricity supply in post-disaster rural areas represents a critical challenge due to damage to the main distribution infrastructure. This article analyzes the potential and provides technical recommendations for implementing renewable-energy-based microgrids as a solution to enhance energy resilience in post-disaster villages. The study identifies the availability of local renewable energy resources (such as solar, micro-hydro, and biomass), assesses community energy demand, and evaluates the technical and operational feasibility of a microgrid system. The results indicate that integrating renewable energy within a microgrid configuration can deliver a more autonomous, flexible, and adaptive energy supply during emergency conditions. Furthermore, technical recommendations related to system design, management models, and implementation strategies are formulated to support the long-term sustainability of microgrid operations. In conclusion, renewable-energy-based microgrid deployment offers strategic potential for strengthening village-level energy resilience in post-disaster contexts while simultaneously promoting a broader transition toward sustainable energy systems.